(untitled) - Cameron, Deborah (Cambridge [England], 2003)
This accessible book looks at how we talk about sex and why we talk about it the way we do. Drawing on examples that range from personal ads to phone sex, sado-masochistic scenes to sexual assault trials, this work provides a clear introduction to the relationship between language and sexuality. Using a broad definition of "sexuality", it encompasses not only issues surrounding sexual orientation and identity, but also questions about the discursive construction of sexuality and the verbal expression of erotic desire
Keywords: Language and sex,Gays,Lesbians,Ngôn ngữ và giới tính,Đồng tính nam,Đồng tính nữ; Language,Language,Ngôn ngữ,Ngôn ngữ